Changes in peripheral mitochondrial DNA copy number in metformin-treated women with polycystic ovary syndrome: a longitudinal study - Yang, Po-Kai; Chou, Chia-Hong; Chang, Chin-Hao; Chen, Shee-Uan; Ho, Hong-Nerng; Chen, Mei-Jou (Reproductive biology and endocrinology, 2020)
Patients with polycystic ovarian syndrome (PCOS) are associated with known alterations in mitochondria DNA copy number (mtDNA-CN). The aim of this study is to study the change in mtDNA-CN in patients with PCOS who were treated with metformin. This is a prospective cohort of patients with PCOS, who received metformin for one year. From 2009 to 2015, 88 women diagnosed with PCOS, based on the Rotterdam criteria, were enrolled. Serial measurements of mtDNA-CN, 8-hydroxydeoxyguanosine (8-OHdG), anthropometric, metabolic, endocrine, and inflammatory markers were obtained before and after 3, 6, and 12 months of treatment. A significant decrease in mtDNA-CN was seen over the course of one year. Other markers, including 8-OHdG, testosterone, free androgen index, blood pressure and liver enzymes, also decreased in the same interval. On regression analysis, there was a significant association between the change in mtDNA-CN and serum total testosterone, and no association between mtDNA-CN and metabolic factors. Treatment with metformin is associated with a time-dependent decrease in mtDNA-CN in patients with PCOS who are treated over the course of one year. This may signify a reduction in mitochondria dysfunction. The change in mtDNA-CN corresponds to a similar change in serum total testosterone, and suggests a possible relationship between mtDNA-CN and testosterone. ClinicalTrials.gov , NCT00172523 . Registered September 15, 2005.